Second training workshop on research to inform agricultural and food security policy and practice in Kenya, 7–9 May 2018 - Karugia, Joseph T. (International Livestock Research Institute, 2018)
The International Livestock Research Institute (ILRI) and the Swedish AgriFoSe2030 programme, are implementing an initiative to develop the capacity of recent PhD graduates to undertake policy relevant research and analysis and disseminate their work to the policy-making community in support of agriculture and food security in Kenya. In this regard, ILRI and AgriFose2030 organized the second 3-day training workshop titled “Research to inform agricultural and food security policy and practice in Kenya” at ILRI Campus, Nairobi on 7th – 9th May 2018. The beneficiaries of the capacity development initiative are drawn from public universities and leading research institutions in the country. A total of 12 participants (5 male and 7 female) attended the workshop. The training sessions were facilitated by researchers and professors affiliated to Kenyan institutions and ILRI staff. The training gave participants an opportunity to widen their understanding on the following technical areas: generating and using evidence; engagement in policy processes; policy communication and advocacy; and monitoring and evaluating. The topics covered had been identified by the participants during the first workshop held in February 2018.